Legal aspects of lithium recovery from geothermal brine - Pyrzyce Geothermal Plant case study - Kowalewska, Izabela Elżbieta; Worsa-Kozak, Magdalena (Wroclaw University of Technology, 2024)
The growing importance of using geothermal brine as an alternative source of lithium in the context of the dynamic development of new technologies is currently being pointed out. The various aspects involved need to be analyzed to consider the recovery of any element from geothermal water. The most crucial of these, after the purely technical aspects, is the legal framework of the operation. Poland and other countries have no specific legislative regulations for recovering lithium from geothermal brine, as existing activities have focused mainly on salt and heat extraction. This article presents a brief over-view of the worldwide literature and the current status of legal regulations related to lithium recovery from brine in Poland. The paper focuses on selected formal possibilities for the recovery of lithium from the water of the GT-1 BIS borehole owned by Geotermia Pyrzyce sp. z o.o. The study aims to present possible legal pathways for this process. The authors also draw conclusions about the need for new regu-lations to recover lithium from geothermal brine. The paper contributes to the research on developing lithium recovery from unconventional sources. Furthermore, it highlights the need for an appropriate legal framework for such kind of activity not only in Poland but in other countries as well.
Mining Science, Vol. 31, 2024, s. 163-181
Keywords: mining; geology; geo-engineering